Coping with Growth Transitions: The Case of Chinese Family Businesses in Singapore - TAN, Wee-Liang (Institutional Knowledge at Singapore Management University, 2001)
Families control more than half of the corporations in East Asia. The contribution of family businesses to Asia's economic growth is predicated upon successfully growing their businesses. Many family businesses in East Asia, spanning countries such as Taiwan, Hong Kong, Indonesia, Singapore, and Malaysia, are Chinese owned and managed. Some claim that these businesses will never develop into full-fledged multinational enterprises because of their cultural heritage (Redding, 1990). However, some Chinese family businesses have successfully made the transition.This paper presents an in-depth study of five Chinese family businesses in Singapore that have successfully made the transition in growth and size and across national boundaries and family generations. Their business empires extend into the Asia Pacific region. This paper highlights the key success factors of these five noteworthy family businesses that enabled them to make these growth transitions.